Metabolic rate of sleeping infants. Issue 4 (October 1996) - Hull, D; McArthur, A J; Pritchard, K; Goodall, M
Abstract : AIM: To measure the sleeping metabolic rate (SMR) of healthy infants in the first year of life. METHODS: The SMR was measured on 73 infants aged 1 to 12 months in a special nursery using indirect calorimetry. One hundred satisfactory observations were made. The room air and radiative temperatures, humidity, and amount of insulation were measured. Parents chose the clothing and bedding that they judged their infant needed. RESULTS: The mean (SD) SMR was 2.4 (0.4) watts (W)/kg or 45 (10) W/m2. The mean SMR of infants aged 1-2 months was 38 compared with 44 W/m2 in infants of 8-12 months; the difference was not significant. There were no obvious differences in SMR between boys and girls. But there were wide differences in SMR between apparently similar infants, range 1.4 to 3.5 W/kg. Most parents selected insulation between 1 and 3 togs, and this was weakly negatively correlated with air temperature. CONCLUSION: These wide variations in SMR mean that it is impossible to give specific guidelines on the amount of clothing and bedding a particular infant will need for thermal comfort in a given room temperature.